Parting Ways with Piano Lessons: Predictors, Invoked Reasons, and Motivation Related to Piano Student Dropouts - King, Karen (Université d'Ottawa / University of Ottawa, 2016)
Piano teachers believe that dropping out before reaching a moderate mastery of the piano is a common problem among students. This study uses Self-Determination Theory to examine three issues related to the high dropout rate from private piano lessons: whether there are predictors associated with dropout, whether low levels of motivation correlate with dropping out, and the primary reasons invoked for stopping lessons. Using the Survey of Musical Interests, 55 former piano students who quit lessons completed a questionnaire with Likert-scale, multiple choice, and open-ended questions, and their parents also filled out a complementary questionnaire. These participants were compared to 153 students and parents who were still involved with piano lessons. Results showed important predictor differences in parental backgrounds, musical ability, and practice habits, and significant differences between the groups’ autonomous motivation. The main reasons invoked for stopping lessons included lack of practice, preferring other instruments, and loss of interest.
Keywords: piano students; motivation; dropout; self-determination theory